Data for Social Good Non-Profit Sector Data Projects - Farmer, Jane; McCosker, Anthony; Albury, Kath; Aryani, Amir (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
"Data collaboration is critical to closing societal gaps in data access and capabilities. Ironically, there is little evidence available about impactful data collaboratives, especially involving non-profits, making their data use challenging. This book fills a void by providing a unique understanding of the variables that matter. Anyone interested in using data for social good should read this book." -Stefaan Verhulst, Co-Founder of The Govlab, New York University and Editor-in-Chief of Data & Policy "The non-profit needs to build data capability so it continues to develop innovative services and report on high impact outcomes. Through practical examples and advice from data projects, this open access book will help make this happen." -Dr Catherine Brown OAM, CEO, Lord Mayors Charitable Foundation, Melbourne, Australia This open access book provides practical guidance for non-profits and community sector organisations about how to get started with data analytics projects using their own organisations' datasets and open public data. The book shares best practices on collaborative social data projects and methodology. For researchers, the work offers a playbook for partnering with community organisations in data projects for public good and gives worked examples of projects of various sizes and complexity. Jane Farmer is Director of the Social Innovation Research Institute at Swinburne University of Technology, Melbourne. Anthony McCosker is Deputy Director of the Social Innovation Research Institute at Swinburne University of Technology, Melbourne. Kath Albury is co-Leader of the Digital Inclusion Program at Swinburne University of Technology Social Innovation Research Institute. Amir Aryani leads the Social Data Analytics Lab at Swinburne University of Technology, Melbourne.